Empire, media, and the autonomous woman a feminist critique of postcolonial thought - De, Esha Niyogi (New Delhi : Oxford University Press, 2011)
Presenting a unique analysis of Indian activist thought through literature, photography, dance drama, television, choreography and cinema, this book argues for a feminist critique of postcolonial thought by looking at the rise of humanism under colonisation and the current influx of neoliberal capitalism.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Women -- India -- Social conditions; Postcolonialism -- India